An Evaluation of the Psychosocial Status of Infertile Women - (:unkn) unknown (My University, 2017)
0

Objective: The aim of this study was to evaluate depression, anxiety, loneliness, and the effects of social support in infertile women in Turkey.Methods: A total of 140 patients who presented at the infertility clinic between June 2012 and December 2012 were included in the study. All of the participants completed the Hamilton Anxiety Rating Scale, the Beck Depression Inventory, the University of California Los Angeles Loneliness Scale, and the Multidimensional Scale of Perceived Social Support.Results: The depression score of the infertile women was lower than that of the general population, and the anxiety score was found to be similar to that of the general population. The loneliness scale score decreased with additional years of marriage and greater monthly income (p<0.05; p<0.05). The social support score also increased with the length of marriage (p<0.05). Two patients were referred to the psychiatry clinic based on the results of the depression scale, and 4 participants were referred based on their anxiety scale scores.Conclusion: Financial circumstances, duration of marriage, and social support influence depression, anxiety, and loneliness in infertile patients. Since there was no significant difference in the level of depression or anxiety in this group of patients, it was concluded that professional support and treatment are only necessary when appropriate
Keywords: Genel ve Dahili Tıp